Метод підвищення завадозахищеності телекомунікаційної системи передачі даних по електромережі - Макаренко, А. О.; Гринкевич, Г. О. (Видавництво Львівської політехніки, 2015)
Розглядається вплив індустріальних завад на симетричні лінії мереж електроживлення, використовуваних для створення багатоканальних систем. Пропонується компенсаційний метод для зменшення впливу індустріальних завад на такі системи. Considered the influence of industrial noise on symmetric lines PowerLine at their use to create multichannel systems. Proposed compensation method to reduce the impact of industrial noise on such systems. For today actively developing telecommunication system, which used PowerLine as a medium of data transfer – boundless information environment, what is used in every home. The main problem in creating specific telecommunication systems is a significant level of external noise that takes from the environment and affect the PowerLine, which in fact is the antenna system. The most significant obstacle is the external noise of natural origin (especially lightning) and industrial noise, which create electric ignition systems of automobiles, fluorescent lamp, lifts, welding machines and other electrical appliances. Industrial noise is a complex process with continuous spectrum, which has a log-normal distribution. Obviously, the spectrum of industrial noise rather broad and does not go beyond 1 GHz. House power system within one electrical substation can be seen as a complex antenna system with multiple parts. To substantially reduce the impact of external interference in symmetrical two-wire line, which is appropriate to use the PowerLine proposed in [8] the method of compensation. It uses special devices that receiving external noise and transmitted it’s in the supply line inverted antiphase signal which compensates interference line taken directly from the environment. That is the total noise spectral density of signal lines equal to 0 and will be made full compensation of noise, which is possible only in theory. But in practice implementation errors do not give the possibility to make full compensation interference, but a significant reduction can be achieved. Connection to line two or more devices of noise compensation through a distance willensure evenly magnitude compensating signal interference. The values of the distance betweenthe devices compensate for interference, and their level at the receiver input terminals requireadditional research and calculations.The results can also be useful when creating telecommunication systems with air lines.
Methods of increase noise immunity telecommunication systems of data transmission mains on of the powerline
Keywords: мережа електроживлення; індустріальні завади; електричне поле; антена; двопровідна симетрична лінія; термінал; компенсація завад; PowerLine; industrial noise; antenna; electric field; symmetrical two-wire line; terminal noise compensation.